HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KOORDINASI MATA TANGAN DENGAN HASIL PUKULAN JUMPING FOREHAND SMASH BULUTANGKIS PADA SISWA PUTRA X TKJ 1 SMK TELKOM PEKANBARU - ', Syafril Syafril; ', Slamet Slamet; ', Yuherdi Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems encountered in boys X TKJ 1 SM Telkom Pekanbaru isIn doing blow smash, students do not by leaps and not on time, so that the blow smashestend to be sharp, not directed properly, and often into the net. Researchers suspect thatthis occurs because students do not maximize the explosive power leg muscle and handeyecoordination to hit a smash badminton resulting blows maximum results. This studywas conducted using a correlation study design aimed to investigate how far thevariables in a factor related to other factors. Correlation is a study designed todetermine the level of relations of different variables in a population, which aims to findout how big the contribution of independent variables and the dependent variable.(Arikunto, 2006: 131). Population is the whole object of research. The population inthis study was the son of X TKJ 1 SM Telkom Pekanbaru many as 16 people. To get thedata in this study used vertical jump test for explosive power leg muscle, throwing testcatch tennis balls to the wall for the hand-eye coordination, and test results of a blowjumping forehand smash badminton. The data obtained in the analysis with a simpleproduct moment correlation. Based on data analysis koifisien correlation of rhitung =0,526 > of rtabel = 0.514. thereby Ha Ho accepted and rejected. It means that there is arelationship between the explosive power leg muscle and hand-eye coordination withthe results of punch jumping forehand smash badminton, where the provision ofcorrelation of a variable with another variable set of rhitung >of rtabel, and significant(Sugiyono, 2008: 258).Keywords: Explosive power, Coordination, Results blow smash, Badminton